Biological Evaluation of Extracts and Triterpenoids of Euphorbia hirta (Biological Sciences - PJSIR, 2005)
Antibacterial and antifungal activities of crude extracts and two triterpenoids, taraxerone (EH-1) and 11a, 12a- oxidotaraxerol (EH-2) isolated from the plant Euphorbia hirta were tested against fourteen pathogenic bacteria and six fungi. Crude extracts and pure compounds exhibited significant activity against most of the bacteria tested. On the other hand, all the crude extracts and pure compounds were active, but not significant enough, against most of the tested fungi. The minimum inhibitory concentrations (MICs) of the isolated compounds were also determined against the tested organisms (107 cells/ml) and the effective values were found to be between 64-128 mg/ml. In the brine shrimp lethality bioassay, the compounds were screened for their probable cytotoxic activity, and the LC values of EH-1 and EH-2 were found to be 17.78 and 10 mg/ml, respectively